2017
DOI: 10.1088/1674-1056/26/12/128701
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic formation mechanism and nanomechanics for the self-assembly process of cross- β peptides

Abstract: Nanostructures self-assembled by cross-β peptides with ordered structures and advantageous mechanical properties have many potential applications in biomaterials and nanotechnologies. Quantifying the intra-and inter-molecular driving forces for peptide self-assembly at the atomistic level is essential for understanding the formation mechanism and nanomechanics of various morphologies of self-assembled peptides. We investigate the thermodynamics of the intra-and inter-sheet structure formations in the self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Since the strength of van der Waals forces is weaker than that of hydrogen bonds, it rarely acts as the main force to promote peptide self-assembly, but always cooperates with other interactions as a driver. Wang and colleages utilized steered molecular dynamics (MD) simulations and umbrella sampling techniques to investigate the formation mechanism of KIIIIK in their study 90 . The findings revealed that the formation of the intra-sheet structure was influenced by both van der Waals and electrostatic interactions, whereas the inter-sheet structure was mainly governed by the van der Waals force.…”
Section: Driving Forces For Co-assemblymentioning
confidence: 99%
“…Since the strength of van der Waals forces is weaker than that of hydrogen bonds, it rarely acts as the main force to promote peptide self-assembly, but always cooperates with other interactions as a driver. Wang and colleages utilized steered molecular dynamics (MD) simulations and umbrella sampling techniques to investigate the formation mechanism of KIIIIK in their study 90 . The findings revealed that the formation of the intra-sheet structure was influenced by both van der Waals and electrostatic interactions, whereas the inter-sheet structure was mainly governed by the van der Waals force.…”
Section: Driving Forces For Co-assemblymentioning
confidence: 99%